Dual‐input and triple‐output boost hybrid converter suitable for grid‐connected renewable energy sources. Issue 4 (1st March 2020) - Mohana Kishore, Pinjala; Bhimasingu, Ravikumar
Abstract : In grid‐connected distributed energy system, power converters are used to integrate different renewable sources and loads. If the number of sources/loads increases, the number of converters/conversions are required. Because of more conversions and operations, the conversion efficiency decreases, and it is difficult to control load/source parameters independently. In order to overcome the problems associated with the integration of multiple sources and loads, this study proposes a dual‐input and triple‐output boost hybrid converter (DTBHC) with independent control. The dual input ports of the proposed converter can be used to connect two different dc voltage sources. Triple output ports of the proposed converter can be used to connect ac grid, ac local loads, and dc local loads. These load voltages are regulated by using carrier‐based modified sinusoidal pulse‐width modulation (CBMSPWM) technique in order to control the dc and the ac loads independently with respect to sources. The DTBHC with CBMSPWM control is simulated using a MATLAB/Simulink ® validated using FPGA controlled laboratory prototype. The validation of the proposed converter is carried out with variation of load current, different input voltages to generate stable ac output voltages (same as well as different frequencies).